A Comparison Study of Alternative Materials to Polycarbonate for the Knee Pad Application - MUHAMMAD NAFIS NAQIUDDIN SHARUDIN; Muhammad A'imullah Abdullah (Progress in Engineering Application and Technology, 2025)
This paper investigates the suitability of thermoplastic polyurethane  (TPU) and thermoplastic elastomer (TPE) as alternative materials for manufacturing knee pads. The goal is to develop a cost-effective, durable, and high-performing alternative to the currently used polycarbonate-based knee pads. Finite Element Analysis (FEA) simulations were performed to evaluate von Mises stress and displacement under impact conditions. TPU and TPE demonstrated superior performance, recording higher stress tolerances and moderate deformation, outperforming conventional Ethylene-Vinyl Acetate (EVA). These findings suggest TPU and TPE are viable materials for cost-effective, protective knee pads.